Defining and improving the rotational and intercropping value of a crop using a plant–soil feedbacks approach. Issue 5 (7th July 2020) - Marques, Edward; Kur, Andi; Bueno, Erika; von Wettberg, Eric
Abstract: Crop rotations and intercropping are an ever‐present sustainable practice across a diverse array of agroecosystems. These management practices can suppress weeds, reduce cycles of disease, build soil organic matter, and increase above‐ and belowground biodiversity, all of which improve the yield of a companion or subsequent crop. Here, we propose the terms 'rotational' and 'intercropping value' as a way to measure the overall effect of these benefits. Additionally, we articulate how to quantify different ecosystem services provided by rotational and intercrops including weed and disease suppression, enhancing microbial communities, and nitrogen fixation using a framework that accounts for how these services support other crops in agroecosystems. By providing a method of identifying and quantifying these rotational and intercropping traits, it may facilitate the breeding of better crops for rotations, for cover cropping, and for intercropping.